Si KB Pintar: An Innovative Media, Empowering Mothers and Husbands for Contraceptive Use and Stunting Prevention - Lia Nurcahyani; Dyah Widiyastuti; Arief Tarmansyah Iman; Yeni Fitrianingsih (Politeknik Kesehatan Kemenkes Surabaya, 2026)
The prevalence of stunting in Indonesia is still high. One of the factors that indirectly causes stunting is maternal factors due to the short distance between births, so, one of the efforts to accelerate the prevention and reduction of stunting is postpartum contraceptive. The problems with the use of contraceptives are unmet need. One of the factors causing unmet need is family planning education and counselling, which is not optimal. Decision-making on family planning is mainly done by the husband, who rarely accompanies his wife during counselling. Researchers have produced Si KB Pintar as a medium that clients and husbands can use to discuss contraceptives after being given family planning counselling. The purpose of the research is to determine the perception and use of contraceptive in Si KB Pintar users. This study uses a mixed-methods design in Cirebon City, Indonesia. The sample used a snowball sampling of 19 people interviewed. Data collection uses semi-structured interviews. The research instruments included Si KB Pintar, in-depth interview guides, voice recorders, and questionnaires. Inductive thematic analysis was carried out, and the data was grouped into several themes, quantitative data (contraceptive use) were analyzed using descriptive statistics. According to the informant, the appearance Si KB Pintar is attractive, complete information, easy to use and understand, a medium for discussing with the husband, very useful, increasing the knowledge of mothers and husbands about family planning, and helping to make decisions about family planning. Most of informants (42%) use the long-term contraceptive method (IUD and Implant).